A PENGAWASAN DALAM MANAJEMEN PENDIDIKAN ISLAM - Rasyidah, Nurhadiati; Masita; Fajrun; Muh. Akbar; Nadi Ratunnaimah; Anisshalihah; Al Raqa (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
This study examines supervision “in Islamic educational management as a strategic function for improving educational quality in a holistic manner, encompassing not only academic achievement but also the development of students’ character and spirituality.” The research addresses three main issues: the concept of supervision in Islamic education, its implementation in quality improvement, and the factors influencing its effectiveness. This study employs a qualitative method with a library research approach, analyzing relevant literature such as books, academic journals, and previous studies. The findings reveal that supervision in Islamic education is systematic, continuous, and holistic, involving control, evaluation, corrective, and preventive functions integrated with Islamic values such as trustworthiness (amanah), honesty, justice, responsibility, and the concept of muraqabah, which strengthens the spiritual dimension. The implementation of supervision includes planning, execution, evaluation, and follow-up actions that are interconnected within a continuous quality improvement cycle. Its effectiveness is influenced by internal factors, including supervisors’ competence, teachers’ professionalism, “and organizational culture, as well as external factors such as educational policies, community support, and technological development. In conclusion, supervision in Islamic educational management is an essential instrument for achieving sustainable improvements in academic, moral, and spiritual quality.